Synthesis of 4-2,7-Dithydroxy Naphthyl Azo-2,3-Dimethyl-1-Phenyl-3-Pyrazoline-5-one . - Sahai, V.M.; Joshi, D.; Pandey, M. (Asian Journal of Chemistry, 2010)
Pyrazoline dye has been synthesised from diazonium salt of 4-amino- 2,3-diamino-1-phenyl-3-pyrazoline-5-one by coupling with 2,7-hydroxy naphthalene. Azo dyes are characterised by the presence of one or more azo (–N=N–) groups. This class of dye is well known for dyeing potentialities and biological activities. The fastness of azo dyes varies widely with structure and environment.